Leader-Follower Distributed Frequency Control for Networked Microgrids Using Model Predictive Control and Graph Theory - Abdelfatah, Mohannad; Tan, Wen-Shan; Raj Irudayaraj, Andrew Xavier; Wu, Yuan-Kang (Conference record of the Industry Applications Conference, 2025)
This paper develops a distributed load frequency control design that employs Model Predictive Control (MPC) within a leader-follower control scheme based on graph theory for networked microgrid (NMG) systems. The proposed NMG model contains three equivalent microgrids (MGs) with fully connected topologies that share tie-lines between them. Each MG includes diesel generators, renewable energy sources, and energy storage systems. The mathematical model was depicted through state-space notations. The frequency control system employed Laplacian-based distributed control, which selected MG1 as the leader to receive information from neighbouring MG2 and MG3, thus minimising communication needs without compromising stability or performance. A basic centralised MPC controller was tested in the model against a variable load for all MGs, and then the results were compared with the proposed distributed MPC (DMPC). The DMPC implementation resulted in superior performance, as it achieved a consistent settling time of just 5 s, which is 2.5 times faster than centralised MPC (12-60 s) and over 28 times faster than PID control (140-180 s), while maintaining steady state error below 0.07 Hz for system frequency control after its testing phase.